Case Study of Effective Cough Implementation in Pulmonary TB Patients in the Nita Community Health Center Working Area - Djara, Frans Loro (Universitas Muhammadiyah Lamongan, 2023)
Introduction: The family is a group of people consisting of father, mother and children, the role of the family is very necessary in helping the healing process of pulmonary tuberculosis. The aim of this study was to determine the role of effective coughing in tuberculosis patients.Methods: Case study analysis was used in this research. two respondents were used in this study to receive intervention while the remaining one respondent did not. This research was analyzed descriptively.Results: After effective cough intervention, tuberculosis patients showed effective results, compared to those who did not receive the intervention.Conclusion: Effective cough intervention is considered safe and improves the patient's ability to expel phlegm.